Apoptosis and associated phenomena as a determinants of the efficacy of photodynamic therapy - Kessel, David (Photochem Photobiol Sci, 2015)
Failure of neoplastic cells to respond to conventional chemotherapy is usually associated with factors that limit access of drugs to subcellular sites, differences in cell-cycle kinetics or mutations leading to loss of drug-activation pathways or other processes that govern response factors. For PDT, efficacy depends mainly on selective uptake of photosensitizers by neoplastic cells, oxygenation levels, the suitable direction of irradiation and the availability of pathways to cell death that are highly conserved among mammalian cell types. While it is possible to engineer PDT-resistant cell types, current evidence suggests that the major obstacles to cancer control relate to drug, light and oxygen distribution. This review discusses some of the factors that can govern PDT-induced cell death.